Influence of Co on the microstructure and mechanical properties of M42 high-speed steel. Issue 1 (1st December 2022) - Wang, Shunduo; Chen, Yunbo; Pan, Peng; Lin, Zhenghua; Zuo, Lingli
Abstract: M42 high-speed steel (W2 Mo9 Cr4 VCo8 ) is a kind of high cobalt super-hard high-speed steel (HSS), which is extensively used in various cutting tool materials, but because of the high price of cobalt, high cobalt HSS does not bring good economic benefits. In this thesis, the consequences of various cobalt contents (0.0%, 2.0%, 4.0%, 6.0%, 8.0%) on the organization and mechanical properties of M42 HSS have been studied. The microstructure of HSS was analyzed by OM, SEM, and EDS, and the Rockwell hardness test, impact toughness test, and flexural strength test were conducted. The results show that cobalt helps to increase the nucleation rate of eutectic carbide precipitation and hinder its growth during tempering of HSS and refine the size of eutectic carbide, and the tempering hardness can be maintained above 68 HRC when the cobalt content is 4%-8%; however, cobalt also significantly reduces the impact toughness of HSS, and each 2% increase in cobalt impact toughness decreases about 4 J·cm −2 . From the point of view of cobalt savings, cobalt content of 4%, high-speed steel tempering hardness, impact toughness, and other mechanical properties can be at a higher level.